1999
DOI: 10.3171/foc.1999.7.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Combined fetal neural transplantation and nerve growth factor infusion: effects on neurological outcome following fluid-percussion brain injury in the rat

Abstract: This study was designed to evaluate the histological and behavioral impact of fetal neural transplantation with and without neurotrophin infusion in rats subjected to traumatic brain injury using a clinically relevant model of lateral fluid-percussion brain injury. Adult male Sprague-Dawley rats received lateral fluid-percussion brain injury of moderate severity (2.1-2.3 atm). Twenty-four hours after injury, minced fetal cortical grafts (E16) were stereotactically transplanted into the site of injury c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Additionally, a number of molecules have been used to enhance the capacity of embryonic stem cells and NPCs to repair CNS damage in animal models of traumatic brain injury. These include trophic factors such as NGF [48], GDNF [49], EGF [50], and FGF2 [7], cytokines such as erythropoietin [51], and also cell adhesion molecules [52–55] and extracellular matrix proteins including tenascin‐R [56]. In these paradigms, introduction of each individual factor resulted in improvement of either cell survival or migration or an increase in the differentiation potential of the transplanted cells towards a desirable pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a number of molecules have been used to enhance the capacity of embryonic stem cells and NPCs to repair CNS damage in animal models of traumatic brain injury. These include trophic factors such as NGF [48], GDNF [49], EGF [50], and FGF2 [7], cytokines such as erythropoietin [51], and also cell adhesion molecules [52–55] and extracellular matrix proteins including tenascin‐R [56]. In these paradigms, introduction of each individual factor resulted in improvement of either cell survival or migration or an increase in the differentiation potential of the transplanted cells towards a desirable pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for a functional role for neurotrophins in the sequelae of TBI can be obtained from studies administering these factors to brain‐injured animals. Intraparenchymal administration of NGF can attenuate cognitive but not neurobehavioural motor deficits or hippocampal cell loss following lateral FP brain injury [ 173, 174] and CCI brain injury in rats [ 40, 41]. Other studies have demonstrated that central NGF administration reduced the extent of apoptotic cell death in septal cholinergic neurons following experimental brain trauma [ 172] and reversed the trauma‐induced reductions in scopolamine‐evoked ACh release [ 40, 41].…”
Section: Brain Trauma and Alzheimer’s Disease: Is Head Injury A Neuromentioning
confidence: 99%
“…Fetal tissue transplanted into the hostile microenvironment of the periinjured cortex after FPI to the brain in adult rats has demonstrated good graft survival, neurite outgrowth across the graft-host interface, attenuation of host neuronal cell death, and improvement in posttraumatic cognitive and motor function. 59,65,67 More specifically, at 4 weeks postinjury, fetal hippocampal grafts correlated with the preservation of ipsilateral hippocampal CA3 region pyramidal cells, and motor function was significantly improved at 2 weeks postinjury compared with injured control animals. 67 Injured rats that Object.…”
mentioning
confidence: 92%
“…59 Despite the ability of fetal tissue to respond appropriately to, and functionally integrate into, the host parenchyma, the major inherent limitations of fetal CNS transplants include their cellular heterogeneity and relative unavailability as well as the potential ethical and practical issues associated with tissue procurement. 16,62,70 Many investigators have recently attempted to find an alternative source of neural progenitor cells or neuronal cells for transplantation that can be characterized, homogeneously expanded, and used for investigating the restorative neurobiological properties of both the surviving host neurons and the transplanted neuronal cells in the setting of brain injury.…”
mentioning
confidence: 99%